Assembly of CRISPR ribonucleoproteins with biotinylated oligonucleotides via an RNA aptamer for precise gene editing. Issue 1 (December 2017) - Carlson-Stevermer, Jared; Abdeen, Amr; Kohlenberg, Lucille; Goedland, Madelyn; Molugu, Kaivalya; Lou, Meng; Saha, Krishanu
Abstract Writing specific DNA sequences into the human genome is challenging with non-viral gene-editing reagents, since most of the edited sequences contain various imprecise insertions or deletions. We developed a modular RNA aptamer-streptavidin strategy, termed S1mplex, to complex CRISPR-Cas9 ribonucleoproteins with a nucleic acid donor template, as well as other biotinylated molecules such as quantum dots. In human cells, tailored S1mplexes increase the ratio of precisely edited to imprecisely edited alleles up to 18-fold higher than standard gene-editing methods, and enrich cell populations containing multiplexed precise edits up to 42-fold. These advances with versatile, preassembled reagents could greatly reduce the time and cost of in vitro or ex vivo gene-editing applications in precision medicine and drug discovery and aid in the development of increased and serial dosing regimens for somatic gene editing in vivo. Using CRISPR to write specific genetic sequences can sometimes be difficult due to the preference of mammalian cells to repair breaks using NHEJ. Here the authors form nanoparticles to localize the template sequence to the nuclease, shifting repair in favor of HDR.